Crime Prevention Through Environmental Design (CPTED): A Review and Modern Bibliography - Cozens, Paul; Saville, G.; Hillier, D. (Emerald Group Publishing, 2005)
This paper reviews the core findings from recently published place-based crime prevention research. It critically evaluates the available evidence on the contribution of Crime Prevention Through Environmental Design (CPTED) as a crime prevention strategy.CPTED is both an increasingly fashionable approach and is being implemented on a global scale (Cisneros, 1995). Additionally, individual components such as territoriality, surveillance, maintenance, access control, activity support and target-hardening are being widely deployed. However, the evidence currently available is inconclusive and much criticised, which effectively prevents widespread intervention and investment in such an approach by central government. The authors detail the difficulties associated with demonstrating the effectiveness of CPTED and conclude that although empirical proof has not been definitively demonstrated, there is a large and growing body of research, which supports the assertion that CPTED is a pragmatic and effective crime prevention tool. This review provides an extensive bibliography of contemporary CPTED and a follow-up paper will discuss the future research priorities for CPTED.